Knowledge and Practice of Breast Self-examination among Women in Yavataml, India, A Cross- Sectional Study - Gore, Sushma; Yelake, Vishal; Dudhe, Mayur (Asian Pacific Journal of Cancer Care, 2022)
Objectives: Worldwide breast cancer is the most common cancer among women. By 2030 the global burden of breast cancer is expected to exceed 2 million, with increasing proportions from developing countries. The aim of this study was to assess awareness about breast cancer among women attending in a gynecological clinic in rural area India. Materials & Methods: It was a cross sectional study done for period of 3months among women attending & Gynae OPD of rural medical college. A total of 460 study participants were enrolled during the study period. Results: About 85% were aware about the disease. Among participants who were aware 41% said its due to obesity, 24.74% said because of genetic,16.32% said due to advancing age and 17.60% said due to inadequate breast feeding. It was observed that 52.80% were aware that biopsy is the first modality of diagnosing breast cancer. And 59.43% were aware about Breast Self-Examination. Conclusion: Awareness about breast cancer among the study participants was good in the present study. Intense health education campaign should be conducted at regular intervals regarding BSE importance. Women should be taught how to do BSE as BSE is the main screening modality which will detect early stage of cancer.